Ultrasound-based abdominal muscles and diaphragm assessment in predicting extubation failure in patients requiring neurointensive care: a single-center observational study - Xiang Qiu; Chuanjuan Chen; Lan Lv; Bihui Yang; Zhiqiang Wang; Jun Ni (Scientific Reports)
Abstract Extubation failure rates are notably high in patients in neurointensive care. Ineffective cough is the variable independently associated with extubation failure, but its quantification remains challenging. Patients with primary central nervous system injury requiring invasive mechanical ventilation were included. After a successful spontaneous breathing trial (SBT), abdominal muscles and diaphragm ultrasound were performed under tidal breathing and coughing. 98 patients were initially recruited for the study, and 40 patients were ultimately included in the final analysis. Extubation failure occurred in 8 (20%) patients. Rectus abdominis (RA) and internal oblique (IO) muscles showed difference regarding cough thickening fraction (TF) between the extubation success and failure group (P < 0.05). The logistic regression that analysis suggested cough TFRA, cough TFIO and cough TIO were the factors associated with extubation outcome (P < 0.05). In the receiver operating characteristic analysis, cough TFIO exhibited the strongest predictive value (AUC = 0.957, 95% CI:0.8979–1). A threshold of cough TFIO ≥ 34.15% predicted extubation success with a sensitivity of 93.8% and specificity of 75%. Abdominal muscles ultrasound was a promising tool to predict extubation for patients requiring neurointensive care. Trial registration: The study was registered on Chinese Clinical Trial Registry: ChiCTR2400088210, Registered 13 August 2024 - Retrospectively registered, https://www.chictr.org.cn/bin/project/edit?pid=234150 .